The Analysis of English Teacher Effort For Evaluating Teacher Performance during Online Learning at Islamic Junior High School: ANALISIS UPAYA GURU BAHASA INGGRIS UNTUK MENGEVALUASI KINERJA GURU SELAMA PEMBELAJARAN ONLINE DI SMP ISLAM - herawati, indri; Taufiq, Wahyu (Universitas Nahdatul Ulama Surabaya, 2022)
Teaching performance evaluation is the way to improve teacher ability, because the teacher performance is effect on the students interesting. There are two ways in evaluating but the formative evaluation is closely related with the teaching performance evaluation. The research purpose is to know how the English teacher effort to apply the teaching performance evaluation during online learning. The research was conducted at SMP Muhammadiyah 10 Sidoarjo in the academic year of 2020/2021 . This research uses qualitative method by conducting the interview and observation to collect the data. The teacher taught by using video conference. The result of the study showed the teacher effort to apply her teaching performance evaluation during online teaching, the researcher can conclude as follow : (1) Considering feedback (2) Collecting classroom observation result (3) Obeying the comment from supervision activity (4) Practicing the plan and improving the plan. Those are the effort to apply teaching performance evaluation that the researcher has conclude. The result that give by this research. First, the research result can help the teacher to apply her teaching performance. Second, for the other researcher it can help them to make a better research about the performance evaluation in teaching English. Key words : Online teaching, performance evaluation, formative evaluation